The Effects of the Movement Tempo on the One-Repetition Maximum Bench Press Results - Wilk, Michal; Golas, Artur; Zmijewski, Piotr; Krzysztofik, Michal; Filip, Aleksandra; Coso, Juan Del; Tufano, James J (Journal of human kinetics, 2020)
Different tempos of movement can be used during resistance training, but programming them is often a trial-and-error practice, as changing the speed at which the exercise is performed does not always correspond with the tempo at which the 1-repetition-maximum occurred. Therefore, the aim of this study was to determine the effect of different movement tempos during the bench press (BP) exercise on the one-repetition maximum (1RM) load. Ninety men (age = 25.8 ± 5.3 years, body mass = 80.2 ± 14.9 kg), with a minimum one year of resistance training experience took part in the study. Using a randomized crossover design, each participant completed the BP 1RM test with five different movement tempos: V/0/V/0, 2/0/V/0, 5/0/V/0, 8/0/V/0 and 10/0/V/0. Repeated measures ANOVA compared the differences between the 1RM at each tempo. The 1RM load was significantly greater during V/0/V/0 and 2/0/V/0 compared to 5/0/V/0, 8/0/V/0, and 10/0/V/0 (p < 0.01). Furthermore, the 1RM load was significantly greater during 5/0/V/0 compared to 8/0/V/0 and 10/0/V/0 (p < 0.01), but there were no differences between either V/0/V/0 and 2/0/V/0 (p = 0.92) or between 8/0/V/0 and 10/0/V/0 (p = 0.08). Therefore, different movement tempos used during training should be accompanied by their own tempo-specific 1RM testing, as slower eccentric phases significantly decrease maximal concentric performance. Furthermore, 1RM test procedures should include information about the movement tempo used during the test protocol. In addition, the standardization of the tempo should be taken into account in investigations that use the 1 RM test to assess the effects of any treatment on maximal muscle strength.
Keywords: eccentric movements; maximal strength; external load; resistance training; duration of repetition